Innovation and Globalization: Benefactors or Barriers to Inclusive Growth? - Khanh Duong; Nguyen Phuc Van (Global Labor Organization (GLO), 2023)
Technological advancements are often viewed as drivers of green growth, but they also carry the potential to widen social inequality, particularly in job automation and the transformation of work routines. This study delves into the relationship between technology and inclusive growth, drawing on global data. We introduce a new concept called 'Inequality-Stabilizing Growth' (ISG), which balances economic progress with social equity. The ISG is calculated by combining factors that both decrease and increase inequality within total growth. Our findings indicate that technology or innovation alone does not necessarily lead to greater social equality or inclusive growth. In developed countries, the transfer of technology supports growth that includes more people, but this is not consistently the case in developing nations. The research also highlights a crucial point: focusing solely on growth without inclusive policies may worsen inequality, hindering future economic development. To counter this, we recommend policies that enhance education and financial growth, adapted to different stages of national development, and include fertility control measures in less developed areas. These factors promote social mobility, which is considered a 'key to curbing inequality.'
Keywords: C33; D63; F63; 330; innovation; globalisation; inclusive growth; unified growth theory